2018
DOI: 10.1177/1071100718764107
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Complications, Reoperations, and Radiographic Outcomes of a New Fixed-Bearing Total Ankle Arthroplasty

Abstract: Level IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 33 publications
7
49
1
Order By: Relevance
“…Some studies report an ideal angle of 90° [10,13,15] and other studies report an ideal angle of 85° [2,9,20]. The mean postoperative tibiotalar angle of 90.1° is comparable to other studies, with a reported mean angle of 88.5° and mean deformity of 1.6° and 3° [2,10,23]. The mean talar alignment of 7.3 mm was in all cases translated anteriorly, which was also found by Choi, et al and Mann, et al [2,20].…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…Some studies report an ideal angle of 90° [10,13,15] and other studies report an ideal angle of 85° [2,9,20]. The mean postoperative tibiotalar angle of 90.1° is comparable to other studies, with a reported mean angle of 88.5° and mean deformity of 1.6° and 3° [2,10,23]. The mean talar alignment of 7.3 mm was in all cases translated anteriorly, which was also found by Choi, et al and Mann, et al [2,20].…”
Section: Resultssupporting
confidence: 78%
“…In literature reoperation procedures vary between 2.9% and 26% [1,2,9,10,13,14,20,[23][24][25]. In this study there were no revisions, which varies between 2.1% and 22.0% in other studies [1,10,11,13,14,20,[23][24][25]. However, the follow-up of the current study was rather short.…”
Section: Resultscontrasting
confidence: 48%
See 3 more Smart Citations